First report of IgE sensitization to Anisakis simplex in a healthy population in Colombia - Jenniffer A. Castellanos-Garzón (Asociación Colombiana de Infectología, 2022)
The anisakiasis is little known in Colombia and rarely diagnosed. However, reports of fish parasitized by anisakid larvae in South America are increasing. Objectives: The objective was determine the prevalence of sensitization to Anisakis simplex in a healthy population in ColombiaMethods: Cross-sectional survey of 150 volunteers from Universidad del Valle's community, Cali, Colombia. Past medical history, including eating habits associated with fish consumption was assessed. Prevalence of IgE antibodies was determined by the ELISA- Trisakis 170 kit for the recombinant allergens Ani s 1 and Ani s 7. Findings: Two sera (1.3%) of blood tested were positive to the Ani s 7 antigen, while for Ani s 1 all sera were negative. Conclusions: This research is the first exploratory study on Anisakis prevalence conducted in Colombia, the results do not indicate a major problem. Nevertheless, more epidemiological studies are needed.